REFORMASI ADMINISTRASI DALAM MANAJEMEN BENCANA - Burhanudin Mukhamad Faturahman (MIMBAR YUSTITIA : Jurnal Hukum dan Hak Asasi Manusia, 2017)
Disaster management is one form of service for the public, which in practice should be managed properly in order to reduce suffering and loss due to a disaster. A descriptive qualitative research shows that changes in mindset and cultural set as initial steps the administration reform in disaster relief in Pacitan Regency need to focus on the activities of the anticipation of disaster which was formed by local stakeholders. This requires awareness of local awareness, commitment, and development efforts are oriented on the anticipation of tsunamis, landslides and flooding.